Temporal variability of secondary processes in alkaline geothermal waters associated to granitic rocks: the Caldes de Boí geothermal system (Spain) - M.P. ASTA; M.J. GIMENO; L.F. AUQUÉ; J.P. GALVE; J. GÓMEZ; P. ACERO; P. LAPUENTE (Geologica Acta, 2017)
The Caldes de Boí geothermal waters show important differences in pH (6.5–9.6) and temperature (15.9ºC–52ºC) despite they have a common origin and a very simple circuit at depth (4km below the recharge area level). Thes differences are the result of secondary processes such as conductive cooling, mixing with colder shallower waters, and input of external CO2, which affect each spring to a different extent in the terminal part of the thermal circuit. In this paper, the secondary processes that control the geochemical evolution of this system have been addressed using a geochemical dataset spanning over 20 years and combining different approaches: classical geochemical calculations and geochemical modelling. Mixing between a cold and a thermal end-member, cooling and CO2 exchange are the processes affecting the spring waters with different intensity over time. These differences in the intensity of the secondary processes could be controlled by the effect of climate and indirectly by the geomorphological and hydrogeological setting of the different springs. Infiltration recharging the shallow aquifer is dominant during the rainy seasons and the extent of the mixing process is greater, at least in some springs.Moreover, significant rainfall can produce a decrease in the ground temperature favouring the conductive cooling. Finally, the geomorphological settings of the springs determine the thickness and the hydraulic properties of the saturated layer below them and, therefore, they affect the extent of the mixing process between the deep thermal waters and the shallower cold waters. The understanding of the compositional changes in the thermal waters and the main factors that could affect them is a key issue to plan the future management of the geothermal resources of the Caldes de Boí system. Here, we propose to use a simple methodology to assess the effect of those factors, which could affect the quality of the thermal waters for balneotherapy at long-term scale. Furthermore, the methodology used in this study can be applied to other geothermal systems.